Aliotto, Marie (audio interview #3 of 3) - Aliotto, Marie (b. 9/5/1903 - d. 5/9/1993); Feichtinger, Kris, interviewer
INTERVIEW DESCRIPTION - This is the final interview conducted with Marie Aliotto as part of a series on the Chicago Women's Local (275). The interview was conducted by Kris Feichtinger, in cooperation with the Feminist History Research Project in Los Angeles. The details of the recording session are unknown. TOPICS - early attitudes towards ACWA and Local 275; career with ACWA and Local 275; Social and Athletic Club; friendships and social activities; working conditions and shop environment; Local 39 and Local 270; Clara Leon; Rose Falk; Sophie Kolbash; Local 275 Dramatic Club, Choir, and Bowling League; and employment experiences at Shapiro's and Progress Tailoring Company;job skills; wages; work ethic; clothing manufacturing; C;B; Shane & Company; Progress Tailoring Company; Shapiro's; ACWA organizing drive of 1919 and her decision to join the union; ACWA employment office and unemployment insurance; 10/30/1974